Microenvironment-Responsive Magnetic Nanocomposites Based on Silver Nanoparticles/Gentamicin for Enhanced Biofilm Disruption by Magnetic Field - Wang, Xi; Wu, Juan; Li, Peili; Wang, Lina; Zhou, Jie; Zhang, Gaoke; Li, Xin; Hu, Bingcheng; Xing, Xiaodong (ACS applied materials & interfaces, 2018)
Biofilms contribute to persistent bacterial infections as well as formidable resistances to conventional antibiotics. However, it is still a major challenge to establish an advanced antibacterial nanoplatform that can efficiently eradicate biofilms while overcoming bacterial resistances. Taking advantage of the stimuli-responsive technique and the magnetic guidance strategy, here we present a highly efficient nanoplatform for planktonic inactivation and biofilm disruption. The multilayer films consisting of antibiotic gentamicin (Gen), tannic acid, and silver nanoparticles (AgNPs) were fabricated and coated on magnetic nanoparticles via electrostatic interactions. To achieve controlled drug release and improved biocompatibility, biodegradable hyaluronic acid was capped on the outer surface as a responsive shell. In vitro release profiles suggested that the nanocomposites showed both enzyme and pH-responsive release properties. The nanoplatform could be employed as a powerful nanocarrier for small molecular Gen and AgNPs delivery and on-demand release in response to bacterial infection microenvironment. The nanocomposites also showed satisfying antibacterial capacities against planktonic Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. Intriguingly, with magnetic field navigation (NdFeB, 2000 gauss), the nanocomposites could be guided to handily penetrate into S. aureus biofilm and performed dual-responsive release, showing significantly enhanced biofilm disruption. Moreover, excess reactive oxygen species production resulting from the nanocomposites contributed to the decomposition of biofilm matrix and ultimate biofilm eradication. As a consequence, the ingenious antibacterial nanoplatform could be promising for combating biofilm infections while overcoming bacterial resistances with extra environmental factors such as magnetic field.